Sulfur‐Doped Rhenium Selenide Vertical Nanosheets: A High‐Performance Electrocatalyst for Hydrogen Evolution. Issue 19 (22nd August 2018) - Xia, Yufei; Huang, Jianwen; Wu, Wenqi; Zhang, Yadong; Wang, Hao; Zhu, Juntong; Yao, Junjie; Xu, Li; Sun, Yinghui; Zhang, Li; Lu, Ruifeng; Xiong, Jie; et al.
Abstract: Developing highly efficient electrocatalysts for hydrogen generation from water has been a crucial option for future energy conversion and storage. Rhenium dichalcogenides (ReX2, X=S or Se) have attracted tremendous research interests due to their unique distorted‐1T phase and anisotropic electronic structure. So far, there is no report about S doped ReSe2 electrocatalyst. In this work, we present a three‐dimensional nanosheets electrocatalyst derived from sulfur‐doped rhenium selenide (ReSe2(1–x) S2x ) grown on carbon fiber paper (CFP) for water splitting. It is noting that the catalytic activity could be significantly fine‐tuned by controlling quantity of sulfur dopant. ReSe1.78 S0.22 /CFP cathode exhibits the best performance with a Tafel slope of 84 mV dec −1, an overpotential of 123 mV to drive the current density of 10 mA cm −2 as well as a long‐term stability of 30 h. The X‐ray photoelectron spectroscopy and density functional theory calculations confirm that sulfur‐doped structure, especially the dangling sulfur atoms adsorbed on the surface Se atom kars, achieves a more thermoneutral hydrogen adsorption energy, conducing an optimized catalytic activity of the basal plane. This study demonstrates that S doped ReSe2 could be a promising candidate electrocatalyst for hydrogen evolution. Abstract : Positive for doping : A sulfur‐doped rhenium selenide nanosheets electrocatalyst is developed for efficient hydrogen evolution, supported by experimental analyses and theoretical simulation.